Rectal Atresia and Congenital Hypothyroidism: An Association or Coincidence? - Mehmetoğlu, Feride (European Journal of Pediatric Surgery Reports, 2018)
Rectal atresia is a rare anorectal malformation, and its association with other anomalies is even more rare. This study presents a unique case of co-twin in which the surviving newborn male underwent surgery due to rectal atresia. Newborn screening tests identified congenital hypothyroidism. The surgical treatment consisted of three stages and thyroid hormones were replaced.
Keywords: rectal atresia; congenital hypothyroidism; posterior sagittal approach